(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores how modern English children’s literature, focusing on Joanne Rowling’s "Harry Potter" novel, blends elements of fantasy and reality. It suggests that incorporating realistic elements like place names, animal names, plant names, characters, scientific principles, and natural phenomena in fantasy narratives bridges the gap between the fantastical and the real. This fusion ultimately fosters a harmonious coexistence of both realms.